Toward a Learning Society Revisited: The Rise and Fall of an Educational Ideal? - Amy D. Rose (Adult Education Research Conference, 2010)
This study begins a broad historical dialogue on the movement for lifelong learning and the “learning society” and the ways that many of the innovations were adopted, while the adult students continued to be marginalized both institutionally and conceptually within adult higher education.